A resting-state fMRI cross-sectional study of cardiorespiratory fitness decline after stroke - Qingming Qu; Kexu Zhang; Hewei Wang; Hewei Wang; Jie Zhu; Jie Zhu; Yingnan Lin; Jie Jia; Jie Jia; Jie Jia (Frontiers in Neurology, 2025)
ObjectiveThe present study aimed to investigate alterations in neural activity and reorganization of functional networks within critical brain regions associated with reduced cardiorespiratory fitness (CRF) in stroke patients. By employing resting-state functional magnetic resonance imaging (fMRI), we sought to identify specific brain areas that may be implicated in CRF decline among this patient population.MethodsA total of 22 patients with stroke and 15 healthy subjects matched for age, gender, and body mass index were recruited. Rehabilitation assessments included peak oxygen uptake (VO2peak), peak work-rate, 10-meter walk test (10mWT), five times sit-to-stand test (FTSST), and 6-min walking distance (6MWD). Resting-state fMRI data were collected for the two groups, and correlation between changes in the amplitude of low-frequency fluctuations (ALFF) and CRF was analyzed to detect brain regions related to CRF and local neural activity in patients with stroke. On the basis of ALFF analysis, brain network analysis was performed, and the CRF-related brain regions in patients with stroke were selected as seed points. Functional connectivity (FC) analysis was the used to identify brain regions and networks potentially associated with CRF in patients with stroke.ResultsPatients with stroke exhibited significantly lower VO2peak, peak work-rate, 10mWT, and 6MWD compared to healthy controls (p < 0.001). FTSST was significantly higher in patients with stroke than healthy controls (p < 0.001). ALFF analysis identified CRF-related brain regions in patients with stroke, including the ipsilesional superior temporal gyrus (r = 0.56947, p = 0.00036), middle frontal gyrus (r = 0.62446, p = 0.00006), and precentral gyrus (r = 0.56866, p = 0.00036). FC analysis revealed that the functional connectivity of brain regions related to CRF in patients with stroke involved the ipsilesional M1 to ipsilesional precentral gyrus and contralesional postcentral gyrus, and the correlation coefficients were r = 0.54802 (p = 0.00065) and r = 0.49511 (p = 0.0025), respectively. The correlation coefficients of ipsilesional middle frontal gyrus to contralesional middle frontal gyrus, angular gyrus and ipsilesional superior frontal gyrus were r = 0.58617 (p = 0.00022), r = 0.57735 (p = 0.00028), and r = −0.65229 (p = 0.00002), respectively.ConclusionThis study observed that CRF levels were lower in stroke patients compared to those in healthy individuals. Resting fMRI analysis was applied to identify CRF-related brain regions (ipsilesional superior temporal, middle frontal, precentral gyri) and networks in patients with stroke.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=151095.